Vibration characteristics of smart laminated carbon nanotube-reinforced composite cylindrical shells resting on elastic foundations with open circuit. (May 2023) - Bisheh, Hossein
Abstract: This study analyzes the vibration of smart laminated carbon nanotube (CNT)-reinforced composite cylindrical shells integrated with piezoelectric materials and resting on elastic foundations. The effect of open circuit electrical boundary condition on vibration characteristics is investigated when a quadratic variation is considered for the electrical potential. Furthermore, the elastic foundations are included in the mathematical modeling to see their effects when the open circuit electrical boundary condition is applied. The first-order shear deformation shell theory and Maxwell's static electricity equation are employed to derive the governing equations, and natural frequencies are calculated by solving an eigenvalue problem. Vibration characteristics with the open circuit electrical boundary condition are compared with those of closed (short) circuit electrical boundary condition for various mechanical boundary conditions and shell and piezoelectric geometrical parameters. The results demonstrate that the open circuit electrical boundary condition leads to higher frequencies than the closed circuit condition and it must be noticed in the design of smart composite structures with embedded or surface-bonded piezoelectric materials.